2020
DOI: 10.1097/tp.0000000000003485
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Transplantation in HIV-positive Patients: Current Practice and Management Strategies

Abstract: The spectrum of renal pathology in HIV-positive individuals is diverse, including lesions directly related to intrarenal HIV gene expression and lesions related to comorbidities, ReviewBackground. HIV-positive patients had been successfully transplanted for the last 15 y and the donor pool had successfully been expanded to also include HIV-positive donors. Methods. We aimed to evaluate the effectiveness of transplantation in HIV-positive patients and highlight some of the important issues reported in the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 49 publications
(85 reference statements)
2
21
0
Order By: Relevance
“…According to overseas data, the graft survival rate of HIV-infected kidney transplant recipients after ART is 90.4% and 73.7% at 1 and 3 years, respectively, with survival rates of 94.6 and 88.2% at 1 and 3 years, respectively [9]. These data are similar to the prognosis for HIV-negative kidney transplant patients [2]; however, we could not find data for Japan. Acute kidney injury associated with HIV includes the direct nephrotoxicity of indinavir and tenofovir used for ART [10].…”
Section: Hiv Complication Screening and Treatmentmentioning
confidence: 59%
See 2 more Smart Citations
“…According to overseas data, the graft survival rate of HIV-infected kidney transplant recipients after ART is 90.4% and 73.7% at 1 and 3 years, respectively, with survival rates of 94.6 and 88.2% at 1 and 3 years, respectively [9]. These data are similar to the prognosis for HIV-negative kidney transplant patients [2]; however, we could not find data for Japan. Acute kidney injury associated with HIV includes the direct nephrotoxicity of indinavir and tenofovir used for ART [10].…”
Section: Hiv Complication Screening and Treatmentmentioning
confidence: 59%
“…HIV is a single-stranded RNA virus that infects CD4positive T lymphocytes, and opportunistic infections are likely to occur when CD4-positive T lymphocytes fall below 200/μL. Before introducing antiretroviral therapy (ART), the prognosis of patients who developed AIDS was extremely poor; ART has dramatically improved the prognosis of Japanese patients [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible reasons could include an altered immune response, the effect of the viral reservoir in the transplanted kidney, and drug interactions between immunosuppressive treatments and ART. 22 Recent evidence indicates that PIs may influence graft survival in HIV-positive renal transplant recipients. Sawinski et al 7 reported a 1.8-fold and 1.9-fold increased risk of graft loss and death respectively in 332 HIV-positive kidney transplant recipients in the Scientific Registry of Transplant Recipients database.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, many transplant professionals were willing to accept donors with an additional risk of transmission of infectious or malignant disease although there was no consensus on clinical pathways [1][2][3]. Many centres closed during the height of the pandemic and now have continuation plans in place [4][5][6].…”
Section: Dear Editorsmentioning
confidence: 99%